Immunity to hepatitis C virus: stunned but not defeated. - Klenerman, P; Lucas, M; Barnes, E; Harcourt, G (2002)
Hepatitis C virus (HCV) readily causes a persistent infection, although some individuals spontaneously control infection. 'Successful' immune responses appear to be multi-specific and sustained-including a major role for CD4(+)T cells. Some antiviral CD8(+)T cells show reduced capacity to secrete antiviral cytokines either temporarily ('stunning') or in the long term ('stunting'). The co-ordination of multiple immune effector functions may be required to gain control of HCV.